Sphingosine 1-phosphate Stimulates Insulin Secretion and Improves Cell Survival by Blocking Voltage-dependent K+ Channels in β Cells - Liu, Zhihong; Yang, Huanhuan; Zhi, Linping; Xue, Huan; Lu, Zhihong; Zhao, Yanli; Cui, Lijuan; Liu, Tao; Ren, Shouan; He, Peifeng; Liu, Yunfeng; Zhang, Yi (Frontiers in Pharmacology, 2021)
Recent studies suggest that Sphingosine 1-phosphate (S1P) plays an important role in regulating glucose metabolism in type 2 diabetes. However, its effects and mechanisms of promoting insulin secretion remain largely unknown. Here, we found that S1P treatment decreased blood glucose level and increased insulin secretion in C57BL/6 mice. Our results further showed that S1P promoted insulin secretion in a glucose-dependent manner. This stimulatory effect of S1P appeared to be irrelevant to cyclic adenosine monophosphate signaling. Voltage-clamp recordings showed that S1P did not influence voltage-dependent Ca2+ channels, but significantly blocked voltage-dependent potassium (Kv) channels, which could be reversed by inhibition of phospholipase C (PLC) and protein kinase C (PKC). Calcium imaging revealed that S1P increased intracellular Ca2+ levels, mainly by promoting Ca2+ influx, rather than mobilizing intracellular Ca2+ stores. In addition, inhibition of PLC and PKC suppressed S1P-induced insulin secretion. Collectively, these results suggest that the effects of S1P on glucose-stimulated insulin secretion (GSIS) depend on the inhibition of Kv channels via the PLC/PKC signaling pathway in pancreatic β cells. Further, S1P improved β cell survival; this effect was also associated with Kv channel inhibition. This work thus provides new insights into the mechanisms whereby S1P regulates β cell function in diabetes.